Characteristics of lower leg and foot muscle thicknesses in sprinters: Does greater foot muscles contribute to sprint performance? - Tanaka, T.; Suga, T.; Imai, Y.; Ueno, H.; Misaki, J.; Miyake, Y.; Otsuka, M.; Nagano, A.; Isaka, T. (European Journal of Sport Science, 2019)
The present study aimed to determine the differences in thicknesses of the lower leg and foot muscles between sprinters and non-sprinters and to examine the relationship between these muscle thicknesses and sprint performance in sprinters. Twenty-six well-trained sprinters and 26 body size-matched non-sprinters participated in this study. Total 9 muscle thicknesses of bilateral lower leg and foot muscles in participants were measured using ultrasonography. Regarding the lower leg muscles, thicknesses of the tibialis anterior, gastrocnemius medial, and gastrocnemius lateral were measured. Regarding the foot muscles, thicknesses of the flexor digitorum longus, flexor hallucis longus, peroneal longus and brevis, abductor hallucis, flexor digitorum brevis, and flexor hallucis brevis were measured. Most muscle thicknesses were significantly larger in sprinters than in non-sprinters. The differences in mean thicknesses of both legs between the two groups were greater in the foot muscles, where it ranged from 10.2% to 17.1%, than in the lower leg muscles, where it ranged from -0.9% to 9.4%. Among foot muscles, the thickness of only the abductor hallucis was positively correlated with the personal best 100-m sprint time in sprinters (r = 0.419, P = 0.033), indicating that a greater abductor hallucis may be a negative factor for superior sprint performance. These findings suggest that although the foot muscles in addition to the lower leg muscles are more developed in sprinters than in non-sprinters, these muscle sizes may not contribute to achieve superior sprint performance.